Computational Thermal Analysis of AISI 1018 Low-Carbon Steel during Gas Tungsten Arc Welding - Orhorhoro, Ejiroghene Kelly; Oghoghorie, Oghenekevwe (FUDMA Journal of Sciences, 2026)
The thermal behaviour of AISI 1018 low-carbon steel during Gas Tungsten Arc Welding (GTAW) is thoroughly investigated computationally in this work utilising computational fluid dynamics and finite volume methods. The study assesses how heat input affects the welded region's temperature distribution, thermal conductivity, dynamic viscosity, specific heat capacity, weld pool behaviour, and heat flux properties. To replicate actual welding conditions, a three dimensional transient thermal model with temperature dependent thermophysical characteristics and a Gaussian moving heat source was created. The findings show that GTAW offers localised heating, controlled thermal penetration, reduced heat affected zone, and improved weld quality. The study provides important insight for optimising GTAW parameters and improving thermal management in steel fabrication industries. The simulation results showed peak temperatures exceeding 4000 K within the fusion zone, confirming stable weld pool formation and effective heat penetration. Thermal conductivity and dynamic viscosity decreased with increasing temperature, while specific heat capacity increased significantly, influencing heat diffusion and molten metal flow. As the temperature rose, specific heat capacity dramatically increased, affecting heat diffusion and the flow of molten metal, but thermal conductivity and dynamic viscosity decreased. The results show that GTAW offers enhanced weld quality, reduced heat affected zone, regulated thermal penetration, and localised heating. The study offers important information for enhancing heat management in steel manufacturing businesses and optimising GTAW parameters.
Keywords: Gas Tungsten Arc Welding; AISI 1018 Low-Carbon Steel; Thermal Behaviour; Computational Fluid Dynamics; Finite Volume Method; Weld Pool Dynamics